Partisipasi Masyarakat Dalam Pengelolaan Daya Tarik Wisata Espa Yeh Panes Natural Hot Spring Resort Di Desa Penatahan Tabanan - Putu Widya Darmayanti; Saptono Nugroho (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2017)
Espa Yeh Panes Natural Hot Spring Resort is natural tourist attraction located in Penatahan vilage, Tabanan regency.Espa Yeh Panes Natural Hot Spring Resort has uniqueness such as hot springs tourist attraction with the beautiful scene.The research study aimed to provide an overview about the community participation typology in management of Espa Yeh Panes Natural Hot Spring Resort. The research method used is qualitativeand quantitavive.The theory and concept used are concept of tourist attraction, concept of management and theory of participation typology in participation.To answer the research questions, data collection was conducted through observation, interviews, and literature study.The sampling techniques used were purposive sampling. Data were analyzed by using descriptive qualitative analysis such as reduction data, collection data and verification. The analysis show that community participation typology in the management of tourist attraction in Espa Yeh Panes Natural Hot Spring Resort is induced participation because because local community invite to involve by PT Sentra Tirta in management of tourist attraction in Espa Yeh Panes Natural Hot Spring Resort.The characteristic of induced participation in Espa Yeh Panes Natural Hot Spring Resort is top-down, local community get sharing to benefit, local community hear and be heard but their views are not necessarily considered by decision-makers and feedback from the local community. Therefore, people need to be empowered in management of tourist attraction in Espa Yeh Panes Natural Hot Spring Resort to get benefit from the development of tourism in the region. Keywords:Participant,Community,Management